Sistem Distribusi Air di Subak Batan Badung, Daerah Irigasi Taman Ayun, Kecamatan Mengwi, Badung - PUTRA, I WAYAN ADJOES BASKARA; ASTITI, I WAYAN SRI; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p17, 2023)
Water Distribution System In Subak Badung, Irrigation Area Taman Ayun, Kecamatan Mengwi, Badung In the Subak Batan Badung area, there is a social conflict between subak members and the community around the subak area. To avoid conflicts over water use, it is necessary to take into account the water needs of each area in the irrigation area. The purpose of the study was to determine the distribution system of the Taman Ayun irrigation area and to avoid social conflicts. This study uses seven informants, and data collection by deepening, observation, and documentation. The data analysis used is descriptive qualitative analysis. The distribution system of Subak Batan Badung has a tertiary irrigation canal that draws water from the Taman Ayun Dam. A careful tertiary channel flows through the Batan Badung subak which consists of three munduks, namely Batan Badung munduk, Batu Tegeh munduk and Batu Lumbung Munduk. Irrigation water from the Taman Ayun weir flows through a tertiary channel and then flows into Tembuku Gede where the flow from Tembuku Gede enters the worm channel which has been arranged by Pekaseh then the clian munduk divides the water for krama subak, every 10 lands get 10 cm of pressure. Boobs are the four-finger count of a farmer's hand in a wormhole. The remaining air will be channeled to Subak Bringkit, if Subak Bringkit needs air. Preventing conflict is carried out, among others, through efforts to make peace in the community, develop peace in a peaceful manner, consider potential conflicts, and build an early warning system. Handling ofconflict when a conflict occurs is carried out through cessation of physical efforts, determination of the status of the state of conflict, emergency action and protection of victims. and/or the deployment and use of the force of the apparatus that uses.